1994
DOI: 10.1111/j.1365-2621.1994.tb08114.x
|View full text |Cite
|
Sign up to set email alerts
|

Textural Properties of Chicken Frankfurters with Added Collagen Fibers

Abstract: Chicken frankfurters made with 0, 2, 4, 6, 8% added collagen fibers and 10, 15, 20, 25, 30% added water were evaluated for textural differences using a torsion test and sensory texture profile analysis. Frankfurters with high amounts of added water and low amounts of collagen fibers had lower shear stress values. Sensory analysis indicated that both collagen fibers and added water had significant influences (PCO.05) on hardness, springiness and juiciness. The addition of collagen fibers resulted in harder, spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 11 publications
5
21
0
3
Order By: Relevance
“…Water levels had effects (Table 4) on sensory hardness (p = 0.0001), springiness (p = 0.01), juiciness (p = 0.002), as well as instrumental Hardness (p = 0.0002), Springiness (p = 0.0001) and Cohesiveness (p = 0.01), and had a marginal effect on sensory cohesiveness (p = 0.06). This confirmed report of Lanier et al (1986) and Meullenet et al (1994) that the amount of water had little influence on sensory cohesiveness, because it did not affect the protein matrix formation. The amount of water added had no effect on cohesiveness of mass (p = 0.35) and wheat flavor (p = 0.17).…”
Section: Texture Of Msp Smoked Sausage supporting
confidence: 94%
“…Water levels had effects (Table 4) on sensory hardness (p = 0.0001), springiness (p = 0.01), juiciness (p = 0.002), as well as instrumental Hardness (p = 0.0002), Springiness (p = 0.0001) and Cohesiveness (p = 0.01), and had a marginal effect on sensory cohesiveness (p = 0.06). This confirmed report of Lanier et al (1986) and Meullenet et al (1994) that the amount of water had little influence on sensory cohesiveness, because it did not affect the protein matrix formation. The amount of water added had no effect on cohesiveness of mass (p = 0.35) and wheat flavor (p = 0.17).…”
Section: Texture Of Msp Smoked Sausage supporting
confidence: 94%
“…Hardness, adhesiveness and gumminess of test samples were moderately altered as compared to control samples whereas, springiness, cohesiveness, chewiness, and resilience were slightly altered. Similar results were observed in case of chicken frankfurters made with added collagen (Meullenet et al, 1994). These results clearly indicate that incorporation of collagen in paneer does not alter its textural attributes extremely.…”
Section: Texture Profile Analysis Of Paneersupporting
confidence: 93%
“…However, the moisture, protein and fat contents between control and GT incorporated cooked sausage did not differ significantly. The addition of GT only slightly affected the composition of the final product, which was in agreement with Meullenet et al, (1994) who reported a small dilution effect in chemical analysis with the addition of collagen rich materials in the formulation of chicken frankfurters.…”
Section: Results and Discussion Physico -Chemical Characteristicssupporting
confidence: 90%